Trafficking in Persons as a Violation of Human Rights in Batam City - Aditya Surya Dinata; Muhammad Hafiz; Nurmadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
In Indonesia, human trafficking is still rife. Cases of human trafficking are still rife in Indonesia. Women and children are the most vulnerable groups to become victims of trafficking in persons. It was found that the motives driving the rampant cases of trafficking in persons in Batam city were economic, family, social and coercive motives. The purpose of this study is to analyze and provide information about the dangers of human trafficking because it is a violation of human rights (HAM)